Simulation of Radiation Effects in AlGaN/GaN HEMTs. (24th January 2015) - Patrick, Erin E.; Choudhury, Mohua; Ren, Fan; Pearton, Stephen J.; Law, Mark E.
Abstract : AlGaN/GaN high electron mobility transistors (HEMTs) are desirable for space applications because of their relative radiation hardness. Predictive modeling of these devices is therefore desired; however, physics-based models accounting for radiation-induced degradation are incomplete. In this work, we show that a partially ionized impurity scattering mobility model can explain the observed reduction in mobility. Electrostatic changes can be explained by confinement of negative charge near the 2DEG in the GaN buffer layer. Simulation results from FLOODS (a TCAD simulator) demonstrate that partial ionization of donor traps is responsible for this phenomenon. Compensation of the acceptor traps by the ionized donors in the GaN confine the acceptor traps (negative space charge) to a thin layer near the AlGan/GaN interface. The simulation results show that near equal concentrations of acceptor traps and donor traps of 1 × 10 17 cm −3 can account for the performance degradation of HEMTs given 5 MeV proton radiation at a fluence of 2 × 10 14 cm −2 . Our results imply that device performance can be accurately simulated by simultaneously accounting for mobility and electrostatic degradation in TCAD solvers using the presented approach.